Engagement Opportunities and Challenges of Transdisciplinary Practice: The 1890 Land-Grant Perspective - Terrence W. Thomas; Alton Thompson (The University of Alabama, 2022)
Land-grant universities' philosophy of education assumes the triumvirate of education, research, and service will produce an improved quality of life and wealth-creating synergies disseminated to communities through Cooperative Extension (Gavazzi & Gee, 2019). In a simpler age, this philosophy worked well. In today's global, technology-mediated, complex society, a transformational overhaul is necessary to amplify and broaden the impact of potential synergies through a robust engagement process. As a path forward, we propose building renaissance transdisciplinary teams, reimagining reward and evaluation systems, and elevating engagement to a position of primacy in strategy and structure. We could elevate Extension to university-wide status and foster engagement as a critical component of teaching (learning) and research (discovery). Using quantitative and qualitative data from the 1890 research directors, Extension administrators, and community stakeholders, we found strong support for greater university engagement with the community, especially for taking a deeper dive into long-term problem-solving by cocreating and codesigning viable solutions. There was also strong support for allocating additional technical and financial resources to build the university's community engagement portfolio. These data also draw attention to the need to elevate community engagement to the level of teaching and research and to establish the presence of the university in the community.